Giant Ovarian Cysts Treated by Single-Port Laparoscopic Surgery: A Case Series - Jiang, Lili; Zhao, Xinyu; Han, Yue; Liu, Kuiran; Meng, Xinyue (Frontiers in Oncology, 2021)
Background： Ovarian cysts are very common diseases of female reproductive system. Giant ovarian cysts refer to the tumors with diameters greater than 10 cm. In recent years, due to the development of clinical diagnosis, imaging modalities and the improvement of patients' cognition of the diseases, the occurrence of giant ovarian cysts become rare. The purpose of this study was to show a new operation method of single-port laparoscopy to treat giant ovarian cysts. Methods: We report a case series of 5 patients with giant ovarian cysts who underwent single-port laparoscopic surgery in gynecology department, Shengjing Hospital of China Medical University between June 2020 and March 2021. The inclusion criteria were ovarian cysts at least 20 cm in diameters, and cases which the tumor might be malignant were excluded. Results: The patients' mean age was 26.2years. The most common clinical presentation was progressive abdominal distension. Median size of the cysts at imaging was 39.2 cm (range 21–63 cm). All patients underwent single-port laparoscopic surgery, and none of them converted to laparotomy. On final pathological reports, two cysts were serous cystadenomas, and three were mucinous cystadenomas. All patients recovered well and discharged on time. Conclusion: Giant ovarian cysts can be treated by single-port laparoscopic surgery. In addition to the well-known advantages of laparoscopic surgery (e.g., small pelvic interference, fast postoperative recovery), it can also play the role of perfect cosmetic results, which has more advantages for young women.